Medicinal cannabis delivery systems: A perspective - Boldrini, Diego Emmanuel (2024)
In recent years, cannabis derivatives have been proposed for the treatment ofvarious medical conditions, including pain, inflammation, epilepsy, sleep disorders,multiple sclerosis, anorexia, schizophrenia, neurodegenerative diseases, nausea,and cancer. While the benefits of cannabis derivatives, primarily cannabinoids,have been demonstrated and continue to be studied, their use presents variouschallenges associated with their low water solubility, rapid metabolism, erraticand poor bioavailability, and erratic pharmacokinetics, which directly affect theirefficacy. In this context, a great deal of research is being carried out to overcomethese drawbacks by designing delivery systems capable of improving solubility/bioavailability, potency, and efficacy, while addressing the purity and quality issuesrequired by the pharmaceutical industry. This article aims to critically review themajor trends and challenges in designing controlled-release cannabinoid deliverysystems and their potential application in the pharmaceutical industry.